2016
DOI: 10.1159/000448687
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Echocardiography and Chest Computed Tomography Arteriography in Patients with Acute Pulmonary Embolism: A Two-Year Follow-Up Study

Abstract: Background: Pulmonary hypertension (PH) is frequently found at the time of diagnosis of pulmonary embolism (PE). An incomplete resolution of PE can lead to chronic thromboembolic pulmonary hypertension (CTPH). Transthoracic echocardiogram (TTE) is the first step to diagnose an abnormality of the pulmonary vasculature. Based on computed tomography (CT), the Qanadli vascular obstruction index has been extensively used to assess acute PE. Objectives: Our aim was to ascertain whether at the time of diagnosis of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…PTE is a significant cause of mortality and morbidity. In previous studies, 90-day mortality rate has been reported as 58.3% in patients with massive PTE and as 15.1% in patients with submassive PTE (11,18). In our study, massive (15.3%) and submassive (6.5%) PTE ratio has been lower than studies where 90 days of mortality have been evaluated.Hospital stay in patients with acute PTE has been reported to vary between 4 and 10 days (19,20).…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…PTE is a significant cause of mortality and morbidity. In previous studies, 90-day mortality rate has been reported as 58.3% in patients with massive PTE and as 15.1% in patients with submassive PTE (11,18). In our study, massive (15.3%) and submassive (6.5%) PTE ratio has been lower than studies where 90 days of mortality have been evaluated.Hospital stay in patients with acute PTE has been reported to vary between 4 and 10 days (19,20).…”
Section: Resultscontrasting
confidence: 51%
“…In our study, however, the prevalence of systemic thrombolytic therapy was higher than those reported in the literature, which could be associated with several factors including the high rate of ICU hospitalization (28.4%), high APACHE II scores and PAP values, and high prevalence of vasopressor requirement, hemodynamic instability, and RVD in our patients. On the other hand, the prevalence of full-dose rtPA therapy was higher than that of half-dose rtPA therapy (56.1% vs. 43.9%) (11,16,17). However, no significant difference was found between these two groups with regard to PAP and the prevalence of RVD, both of which are significant pathfinders in the decision-making processes regarding thrombolytic therapy and its dosage.…”
Section: Resultsmentioning
confidence: 86%
“…Surprisingly, a study proposed that serum NT‐proBNP and troponin T levels can be superior to the combination of biomarkers and right ventricular dysfunction findings in CTPA/echocardiography in risk stratification of patients with normotensive PE 21 . Moreover, one of the well‐known methods is the CT index, which quantifies the arterial obstruction in PE and highly correlates with CTPA findings 22–24 . Further expansion of these noninvasive and operator‐independent methods could help in the early diagnosis of PE and the successful prediction of its adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Moreover, one of the well‐known methods is the CT index, which quantifies the arterial obstruction in PE and highly correlates with CTPA findings. 22 , 23 , 24 Further expansion of these noninvasive and operator‐independent methods could help in the early diagnosis of PE and the successful prediction of its adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%